Pengaruh PBL ( Project Based Learning ) Terhadap Perubahan Dan Pertumbuhan Umkm Oppa Box - Putri, Rorin Selinggo; Ramadhani, Putri Asri; Putra, Ramdani Bayu (CV. ITTC INDONESIA, 2024)
Change management is an important element in managing transformation in organizations, including micro, small and medium enterprises (MSMEs). MSMEs, which are the backbone of the Indonesian economy, face big challenges in dealing with dynamic market, technology and policy developments. And by conducting this research we want to know the influence of PBL (Project Based Learning) on ​​the growth that occurs in OPPA BOX MSMEs so that we can help development and growth of this business.It is hoped that this research will help in innovation in every product developed by OPPA BOX MSMEs.